Áburðargjöf í lífrænni ræktun á Íslandi - 2014 - Stadler, Christina Maria 1975- (2015)
In the past, organic vegetable crops in Iceland were fertilised mainly with mushroom compost (1,9% N). However, due to the contamination with conventional chicken manure this fertiliser is to be replaced. Thus, substitutes are urgently needed. Composted cow manure (1,9% N), residues from the fish industry (10,9% N), and commercial organic fertilisers (216 mg N/l) have been tested in a greenhouse experiment with tomatoes (variety ‘Dirk’). Plants were grown with a plant distance in the row of 49,25 cm, 2,5 plants/m² and 250 kg N/ha fertiliser was applied in a split application within a fertiliser band of 30 cm during a growth period of seven months. The yield of tomatoes was measured and soil samples regularly taken and analysed for nitrate-N. Due to the high soil N supply of the soil in the greenhouse did the fertiliser treatments show no significant differences in tomato yield and even not to the unfertilised control. A tendentially higher yield was reached after application of Pioner complete 6-1-3®. In general was the yield level low. The reason for that was a relatively low natural solar irradiation during the whole growth period compared to other years. A fertiliser application markedly affected the nitrate content in the soil. Also, hand hoeing increased the soil nitrate content and should therefore be part of an optimised fertiliser management strategy. When just observing the price for one kg of N, mushroom compost seems to be a cheap fertiliser. However, when also the N utilisation is considered, both fishmeal and Pioner complete 6-1-3® are even cheaper than mushroom compost. Taking more years into account would probably result in similar values for all fertilisers as mushroom compost is not only mineralising N in the year of application. The prohibition of mushroom compost should not really effect the organic vegetable growers as there are at least equal (composted animal manures) or even better fertilisers (e.g. fishmeal) with a similar price range on the market. Fram til þessa hafa grænmetisbændur í ...